Monophenol Monooxygenase and Lincomysin Biosynthesis in Streptomyces lincolnensis - Michalik, Joanna (1975)
Monophenol monooxygenase (monophenol, dihydroxyphenylalanine:oxygen oxidoreductase EC 1.14.18.1) was studied in melanin-positive and melanin-negative mutants of Streptomyces lincolnensis NCIB 9413, varying in the lincomycin synthesizing ability. The activities of laccase and tyrosine phenol lyase (EC 4.1.99.2) are absent in this organism. The monophenol monooxygenase catalyzes hydroxylation of monophenols (K(m) and V(max) for l-tyrosine, 2 × 10(−4) M and 8.0 nmol of O(2)/min per ml, respectively) at a slower rate than it dehydrogenates diphenols to o-quinones (K(m) and V(max) for l-3,4-dihydroxyphenylalanine, 7 × 10(−5) M and 51.7 nmol of O(2)/min per ml, respectively. It is inhibited by KCN, β-mercaptoethanol, ethylenediaminetetraacetate, dipyridyl, thiourea, p-aminobenzoic acids and by some tryptophan metabolites. Changes in the activity of monophenol monooxygenase caused by mutation or by inhibitors are reflected in the synthesis of the antibiotic. Its participation in the biogenesis of the propylhygric moiety of lincomycin is discussed.